Severity Extent Of Wasting Among Children Admitted To Therapeutic Feeding Program. A Case Control Study - Aida H. Al-Sadeeq; Rozina Khalid (Journal of Pediatric Health And Nutrition, 2024)
Introduction Children with complicated Severe Acute Malnutrtion (SAM) admitted to Therapeutic Feeding Center (TFC), and ‘uncomplicated’ SAM managed in Outpatient Therapeutic Program (OTP). Objective This study aims to examine the anthropometric differences between SAM admitted to TFC and OTP. Methods A hospital based case control study conducted in the Therapeutic Feeding Program (TFP) of Al-Sadaka General Teaching hospital, Aden, included complicated (cases) and uncomplicated (control) severely wasted 6-60 month old children admitted between July 2022 to June 2023. The WHO anthropometric calculator was used to assess every child’s weight-for-length/height SD and length/height for age SD. Results A total of 313 cases and 122 controls were admitted, mean age, weight, length/height, and MUAC among the cases were (13.04±7.34 mo., 5.41±1.33 kg, 68.32±7.10 cm, and 10.57±1.36 cm) respectively; while among the controls were (20.05±12.93 mo., 7.05±1.74 kg, 76.89±10.46 cm, and 11.28±1.11 cm) respectively. Severe wasting by WFL/H < - 3SD z- score seen more among the controls; cases vs controls were (37.0% vs 68.9%). Howevere, the other groups of severity of WFL/H z-score were seen with nearly douple frequencies among the case vs the controls (35.8% vs 18.8% < - 4SD), (14.7 vs 7.4% < - 5SD). Less than – 6SD was seen much more among the cases vs the controls (8.6% vs 1.6%). Less than – 7 SD among the cases was 1.3% and no children belong to this group in the controls.. The majority of the cases belonged to the age group 6-24 months. Conclusion Children a dmitted to TFC had severe wasting reaching up to < - 6 and < - 7 SD below the WHO cut-off, WFL/H < - 3SD z-score, and at an early age, with simultaneous presence of severe stunting and low MUAC which denotes high mortality risk.
Keywords: Anthropometric